This is a pretty straightforward algebra problem.
-9t + 2 = 56
9t = -54
t = -6
I added 9t to both sides and subtracted 56 from both sides. Then I divided both sides by 9.
2007-04-29 14:17:33
·
answer #1
·
answered by DavidK93 7
·
0⤊
0⤋
-56 + 2 = 9t
-54 = 9t
-6 = t
2007-04-29 21:19:10
·
answer #2
·
answered by Norrie 7
·
0⤊
0⤋
Subtract 2 from both sides of the equation for:
-9t=54
Divide both sides of the equation by -9 for:
t= -6
2007-04-29 21:18:14
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
-9t+2=56
-9t=54
t=-6
2007-04-29 21:17:46
·
answer #4
·
answered by *~LiZzY~* 2
·
0⤊
0⤋
t= -6
2007-04-29 21:20:38
·
answer #5
·
answered by Brooke S 1
·
0⤊
0⤋
-9t = 56 -2
-9t = 54
__...__
-9....-9
t = -6
2007-04-29 21:17:50
·
answer #6
·
answered by t_nguyen62791 3
·
0⤊
0⤋
the answer would be -6. subtract the 2 from both sides then dived both sides by -9. you get t=-6
2007-04-29 21:23:01
·
answer #7
·
answered by irulemarys 1
·
0⤊
0⤋
-6
2007-04-29 21:16:16
·
answer #8
·
answered by ROB D 2
·
0⤊
0⤋